ASSESSMENT OF INCIDENCE OF PULMONARY EMBOLISM IN COVID-19 PATIENTS: A SINGLE-CENTER STUDY - RANA, MA; SIDDIQI, MRO; SIDDIQUI, MH; RAZA, A; AWAD, AHA; ABDELBAKY, AM; ELMASRY, WG; HANIF, S (Biological and Clinical Sciences Research Journal, 2023)
Pulmonary embolism (PE) is a life-threatening disease with a high death toll. Recent research has shown that patients with COVID-19 are more likely to experience PE because of the inflammatory reaction and hypercoagulability. This article’s goal is to assess the prevalence of PE among hospitalized COVID-19 patients. We examined the medical files of 210 individuals hospitalized in the COVID-19 unit at Bahria Town International Hospital Lahore between September 1, 2020, and September 30, 2021. Real-time polymerase chain reaction was used to identify COVID-19 in the patients and computed tomography pulmonary angiography (CTPA) was performed to ascertain PE. Of the 210 patients, 9 experienced PE, constituting a 4.3% incidence rate in our study. Our research demonstrates that PE frequently occurs in COVID-19 hospitalized patients. Based on the results, it can be concluded that preventive measures should be considered for people with COVID-19 disease, especially those with a smoking history and low oxygen levels. The fatality rates linked to this illness can be decreased by early diagnosis and timely treatment.